Relationship of normal weight central obesity on comorbid diseases: Systematic Review - Wardah Hanifah; Syahrizal Syarif (AcTion: Aceh Nutrition Journal, 2024)
Normal-weight central obesity (NWCO) has a significant effect on Cardiovascular Disease (CVD) and mortality, which are modulated by comorbidities. This systematic review aimed to identify comorbid diseases associated with NWCO. Search for articles published in 2013-2023 using the PubMed, Science Direct, and Scopus databases. Articles were selected based on the inclusion criteria, specifically articles about the relationship between NWCO and comorbid diseases, using English language, observational study design, and can be accessed in full text. Each article was assessed based on sample size, study design, response rate, outcome measurement, statistical analysis, confounding factors, ethics, and research limitations. The results of this study show that NWCO increases the risk of comorbid diseases such as hypertension, CVD, Diabetes Mellitus (DM), Metabolic Syndrome (MS), dyslipidemia, stroke, and hyperuricemia. Hypertension, MS, and dyslipidemia play a role in the incidence of CVD and DM. This study can increase awareness and attention to groups with normal body weights to improve lifestyle, routine health screening, and immediate intervention to prevent comorbid diseases.